A Simple and Affordable System for Installing Shallow Drive Point Piezometers. Issue 3 (29th April 2015) - Burk, Lawrence; Cook, Peter G.
Abstract This paper describes a drive point system for installing small‐diameter (15 to 25 mm ID) piezometers to depths of several metres in unconsolidated sediments. The system fills the gap between (1) heavy duty drive point systems powered by drilling rig hydraulics or air hammers that are capable of installing large diameter drive points to depths of many tens of metres and (2) manually driven systems that typically install 10 mm ID or smaller tubing to depths of <2 m. Unlike many existing systems, which install piezometers inside an outer casing that is later removed, our system protects the piezometer screen inside the casing and extends it only once the casing is driven to the desired depth. This avoids clogging of the screen during installation and the risk of creating an annulus around the piezometer, which can provide a preferential pathway for water movement. The piezometer has a larger diameter than most manually driven systems, and thus has a higher yield; it also permits use of most commercially available pressure transducers and electrical conductivity sensors. The piezometers have been successfully installed to depths of up to 6 m using an electric hammer. The system overcomes some issues associated with existing systems and provides the advantages of affordability, rapid installation, mechanical assistance and manual portability.